Gender Differences in Ghrelin Association with Cardiometabolic Risk Factors in Arab Population - Mohamed Abu-Farha; Mohammed Dehbi; Fiona Noronha; Ali Tiss; Monira Alarouj; Kazem Behbehani; Abdullah Bennakhi; Naser Elkum (International Journal of Endocrinology)
Ghrelin is a stomach produced hormone that has been shown to have protective role against development of CVD which is a leading cause of death in the Arab world. The objective of this study is to examine the gender difference in association between traditional CVD risk factors and plasma ghrelin among Arabs. 359 Arab residents in Kuwait participated in a cross-sectional survey (≥20 years old): 191 were females and 168 were males. Plasma level of ghrelin was assessed using Luminex-based assay. Ghrelin levels were significantly higher in females (935 ± 78 pg/mL) than males (763 ± 65 pg/mL) (P=0.0007). Females showed inverse association with WC (r=-0.23, P=0.001) and HbA1C (r=-0.19, P=0.0102) as well as SBP (r=-0.15, P=0.0383) and DBP (r=-0.16, P=0.0230), respectively. Higher levels of ghrelin were shown to associate with increased insulin resistance, as measured by HOMAIR, in male Arab subjects (P-trend = 0.0202) but not in females. In this study we show that higher ghrelin level was negatively associated with measures of obesity, HbA1C, and blood pressure in females and positively associated with increased insulin resistance in Arab males.